New altitudinal records of Dasyprocta punctata (Rodentia: Dasyproctidae) in the Eastern Andean mountain forests of Cundinamarca, Colombia - Sergio Andrés Collazos-González; Dennis Castillo-Figueroa; Javier Sunyer; Diego A. Amaya-Hernández; María José Calderón-Ponce De León; Adriano Pérez-Villegas (Mammalogy Notes)
We document three independent records of the Central American agouti (Dasyprocta punctata Gray, 1842) in the Eastern Andes of Colombia, in the villages of La Selva and Mancilla, located in the municipality of Facatativá, Cundinamarca Department. These records were obtained at 2978 and 2982 masl in the upper Andean forests of Colombia, representing one of the highest recorded elevations for this species across its entire distribution.